Faktor–Faktor yang Berpengaruh Terhadap Struktur Modal pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2014 - Andika Fitri; Theresia Purbandari; Intan Immanuela (Fakultas Bisnis, 2018)
This study aims to prove empirically that company size (size), liquidity, profitability, business risk, the sales growth, the structure of assets, debt ratio, and managerial ownership to capital structure on companies listed in Indonesia Stock Exchange in 2013 -2014. The data used in this study was obtained from the company's financial report published on the website of the Indonesia Stock Exchange. The sample in this study was 124 financial statements in accordance with the criteria of the samples (purposive sampling). The hypothesis test uses multiple linear regression analysis with SPSS version 17. The results of this study prove that the variable firm size, asset structure, and the debt ratio has positive effect on the capital structure. The results of this study also proves that managerial ownership variable negative effect on the capital structure. While variable liquidity, profitability, business risk, and sales growth have no effect on the capital structure.